Association between sentinel lymph node biopsy and micrometastasis in endometrial cancer. (August 2022) - Matsuo, Koji; Klar, Maximilian; Khetan, Varun U.; Violette, Caroline J.; Youssefzadeh, Ariane C.; Yessaian, Annie A.; Roman, Lynda D.
Abstract: Objective: Sentinel lymph node (SLN) biopsy is increasingly utilized at surgical staging for early endometrial cancer. This study examined the association between SLN biopsy and micrometastasis in endometrial cancer. Methods: This is a retrospective cohort study examining the National Cancer Institute's Surveillance, Epidemiology, and End Result Program. The study population was 6, 414 women with T1-2 endometrial cancer who underwent primary hysterectomy and surgical nodal evaluation. Exclusion criteria included cases with isolated tumor cells. Exposure assignment was surgical nodal evaluation (SLN biopsy or lymphadenectomy). Main outcome measure was micrometastasis, assessed by inverse probability of treatment weighting propensity score in a stage-specific fashion. Results: In T1a disease ( n = 4, 608), SLN biopsy was performed in 1, 164 (25.3%) cases. SLN biopsy was associated with a 90% increased likeliness of identifying micrometastasis compared to lymphadenectomy (1.3% versus 0.7%, odds ratio 1.90, 95% confidence interval 1.02–3.55, P = 0.040). In T1b disease ( n = 1, 369), 270 (19.7%) cases had SLN biopsy. The incidence of micrometastasis was significantly higher in the SLN biopsy group compared to the lymphadenectomy group (8.4% versus 5.0%, odds ratio 1.74, 95% confidence interval 1.06–2.86, P = 0.028). In T2 disease (SLN biopsy in 57 [13.0%] of 437 cases), the incidence of micrometastasis was similar between the two groups (7.9% versus 7.0%, odds ratio 0.88, 95% confidence interval 0.30–2.60, P = 0.818). Conclusion: This study suggests that SLN biopsy protocol may identify more micrometastasis in the regional lymph nodes of T1 endometrial cancer. Whether national-level increase in the utilization of SLN biopsy for early endometrial cancer results in a stage-shifting to advanced disease on a population-basis warrants further investigation.